Factors associated with stunting and wasting in children under 2 years in Bangladesh. Issue 9 (September 2020) - Chowdhury, Tuhinur Rahman; Chakrabarty, Sayan; Rakib, Muntaha; Afrin, Sabiha; Saltmarsh, Sue; Winn, Stephen
Abstract: Child undernutrition has been a major concern for Bangladesh as it is amongst the highest stunting and wasting prevalent countries in the world. The objective of our study was to explore the socioeconomic determinants of stunting and wasting in children under two years. This study explored nationally representative sample of 7, 230 children ranging in age from 0 to <24 months using two separate binary logistic regression models to determine the risk factors associated with child stunting and wasting. Our study estimated approximately 33 percent children to be stunted and 11 percent to be wasted. Our analysis found that, 12 to <24 months old children's height-for-age-z-score and weight-for-height-z-score deteriorated in comparison to those of below 6 months. Female children had significantly lower odds of stunting and wasting compared with male children. Study revealed that children from wealthier families were at lower risk of being stunted and wasted compared to children from poorer households. Parental education was determined as a significant predictor of stunting. Children who lived in Sylhet division were 1.26 times more likely to be stunted than the children of Dhaka division [OR = 1.26; 95% CI: 1.02–1.55]. Our study revealed age, gender, geographic distribution, and household's position in wealth index as common determinants of child stunting and wasting in Bangladesh. While parental education was significant predictor for child stunting, type of toilet facility was found as statistically significant determinant of child wasting in children of less than two years age. Abstract : Public health; Determinants; Developing country; Growth failure.; Chronic malnutrition; Child undernutrition; Socioeconomic risk factors; Acute malnutrition